Promag-Fit: Platform Digital Pengelolaan Magang Mahasiswa Fakultas Ilmu Terapan - Amelia Yasmin, Rizka; Indah Mega Mandasari, Rizza (eProceedings of Applied Science, 2023)
Abstract— According to Law Number 13 of 2003 concerning Manpower, apprentices are defined as part of a job training system that is held in an integrated manner between trainers in training institutions by working directly under the guidance and supervision of instructors or more experienced workers/laborers, in the process of producing goods. and/or services in the company, in order to master certain skills or expertise. Every year the LKM and the Faculty of Applied Sciences collect data for students who are doing an internship program. Data collection was done manually through Google Form, by registering about 1026 students. The act of collecting data through Google Forms tends to be ineffective both in terms of time and effort. Thus, a digital internship management platform is needed which is expected to help manage internship data by students, lecturers, and LKM. The test results in this final project are that Promag-FIT is able to overcome the main problems in LKM regarding student internship data collection and provide convenience for students during the internship program from registration to assessment.Keywords— job training, internship, internship data, internship management